Implementasi Pengelolaan Dana Pensiun Lembaga Keuangan (DPLK) Pada Bank Muamalat Cabang Pembantu Wonomulyo - Ita Adriani Sari; Rahmi Tria; Miftahurrahman Hafid (STAIN MAJENE, 2026)
This study aims to analyze the implementation of the Financial Institution Pension Fund (Dana Pensiun Lembaga Keuangan/DPLK) management at Bank Muamalat Wonomulyo Sub-Branch Office, identify the challenges encountered, and examine community understanding and participation in Islamic pension fund programs. This research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving branch management, DPLK officers, and participants. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the implementation of DPLK management has been carried out in accordance with Islamic principles through the application of sharia contracts, investment in sharia-compliant financial instruments, supervision by the Sharia Supervisory Board, and the implementation of transparent and accountable governance. Nevertheless, several challenges remain, including limited human resource competence, suboptimal digital system integration, low public literacy regarding Islamic pension funds, and competition with conventional pension products. To address these challenges, Bank Muamalat has implemented continuous staff training, expanded public financial education, strengthened digital services, and collaborated with community and religious leaders. The study concludes that public participation in Islamic pension funds is influenced by Islamic financial literacy, service quality, religiosity, and trust in the institution. These findings contribute to the development of Islamic pension fund management practices and provide recommendations for strengthening public financial literacy and improving institutional governance.